Induction of Protease Activity in Vibrio anguillarum by Gastrointestinal Mucus - Denkin, Steven M. (American Society for Microbiology, 1999)
The effect of gastrointestinal mucus on protease activity in Vibrio anguillarum was investigated. Protease activity was measured by using an azocasein hydrolysis assay. Cells grown to stationary phase in mucus (200 μg of mucus protein/ml) exhibited ninefold-greater protease activity than cells grown in Luria-Bertani broth plus 2% NaCl (LB20). Protease induction was examined with cells grown in LB20 and resuspended in mucus, LB20, nine-salts solution (NSS [a carbon-, nitrogen-, and phosphorus-free salt solution]), or marine minimal medium (3M) (∼10(9) CFU/ml). Induction of protease activity occurred 60 to 90 min after addition of mucus and was ≥70-fold greater than protease activity measured in cells incubated in either LB20 or 3M. Mucus was fractionated into aqueous and chloroform-methanol-soluble fractions. The aqueous fraction supported growth of V. anguillarum cells, but did not induce protease activity. The chloroform-methanol-soluble fraction did not support growth, nor did it induce protease activity. When the two fractions were mixed, protease activity was induced. The chloroform-methanol-soluble fraction did not induce protease activity in cells growing in LB20. EDTA (50 mM) inhibited the protease induced by mucus. Upon addition of divalent cations, Mg(2+) (100 mM) was more effective than equimolar amounts of either Ca(2+) or Zn(2+) in restoring activity, suggesting that the mucus-inducible protease was a magnesium-dependent metalloprotease. An empA mutant strain of V. anguillarum did not exhibit protease activity after exposure to mucus, but did grow in mucus. Southern analysis and PCR amplification confirmed that V. anguillarum M93 contained empA. These data demonstrate that the empA metalloprotease of V. anguillarum is specifically induced by gastrointestinal mucus.